Association between perceived social support and post-traumatic growth among female thyroid cancer survivors: the chain mediating role of psychological resilience and coping strategies - Lyu, Qing; Hu, Yinchu; Kou, Cuimin; Li, Yan; Li, Zhengjiang; Liu, Shaoyan; Fu, Li; Wang, Na (Frontiers in Psychology, 2025)
IntroductionThe incidence of thyroid cancer has exhibited a steady upward trajectory, with women being more prevalent than men. Meanwhile, female thyroid cancer survivors are more prone to encountering negative psychological issues. Post-traumatic growth (PTG), a key element of positive psychology, has not been extensively studied in female thyroid cancer survivors, with unclear development pathways. This study aimed to investigate the correlates of PTG in female thyroid cancer survivors, including perceived social support, psychological resilience, and coping strategies.MethodsSix hundred and thirty-five female thyroid cancer survivors were included in this cross-sectional study. Data were collected using an online questionnaire comprising demographic information and scales measuring perceived social support, psychological resilience, coping strategies, and PTG. The relationships among variables were assessed using Pearson correlation analysis. The potential mediating roles were explored using AMOS 26.0. The indirect effects were assessed through bias-corrected bootstrapping procedure, utilizing 5,000 bootstrap samples.ResultsPerceived social support was directly related to PTG (p < 0.001) in female thyroid cancer survivors. It exerted indirect effects on PTG through the mediating roles of specific coping strategies, including problem-focused coping (effect size = 0.197, p < 0.001), emotion-focused coping (effect size = 0.141, p < 0.001), and avoidant coping (effect size = 0.009, p < 0.05). In addition, chain mediation pathways involving both psychological resilience and coping strategies were identified. Specifically, a significant chain mediation effect was found through psychological resilience and emotion-focused coping (effect size = 0.008, p = 0.002), as well as through psychological resilience and avoidant coping (effect size = −0.003, p = 0.031). In contrast, psychological resilience alone did not serve a significant mediating role between perceived social support and PTG (p > 0.05).ConclusionPsychological resilience and emotion-focused/avoidant coping strategies play a chain mediating role in the relationship between perceived social support and PTG in female thyroid cancer survivors. These findings enhance the understanding of the predictive effects of perceived social support on PTG and suggest ways to enhance PTG among female thyroid cancer survivors.